The Influence of Fundamental and Macroeconomic Analysis on Stock Price - Hari Gursida (STKIP Singkawang, 2017)
The purpose of this research is to analyze the effect of fundamental and macroeconomic analysis on stock price. The research was conducted at a coal company listed on the Indonesia Stock Exchange. Fundamental analysis measured by current ratio, debt to equity ratio (DER), earning per share (EPS), return on assets (ROA), and total assets turnover (TATO), while macroeconomic analysis is measured by inflation and exchange rate. Current ratio (CR) has a positive effect on Stock Price. Strengthening this level of liquidity can provide information to investors to decide to buy shares of companies that tend to be healthy and stable. Return on assets (ROA) has a positive and significant influence on stock price. Efforts to maximize the level of profitability by increasing the value of return on assets can provide information to investors that investments invested in the company will provide good profit. The impact of stock prices will rise. While debt to equity ratio (DER), earning per share (EPS) and total assets turnover (TATO) have no effect on Stock Price. Macroeconomic analysis shows: (a) Inflation rate has no effect on stock price of coal company. This can be because the inflation rate in Indonesia is at the level of 6% -7% per year and included in the category of mild inflation. Mild inflation resulted in very slow economic growth, not affecting stock prices. The exchange rate has a negative and significant effect on coal company stock price. If the Rupiah is depreciated then the stock price of the coal company will decrease.